2012
DOI: 10.1523/jneurosci.4036-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Coding of Spatial Information in the Primate Retina

Abstract: Sensory neurons have been hypothesized to efficiently encode signals from the natural environment subject to resource constraints. The predictions of this efficient coding hypothesis regarding the spatial filtering properties of the visual system have been found consistent with human perception, but they have not been compared directly with neural responses. Here, we analyze the information that retinal ganglion cells transmit to the brain about the spatial information in natural images subject to three resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 67 publications
(154 reference statements)
7
124
0
Order By: Relevance
“…TH and IRN 1/f are thermal and flicker input ise components of the preamplifier's core and s the input referred noise generated by the , R 1 .…”
Section: Recording Channelmentioning
confidence: 99%
See 2 more Smart Citations
“…TH and IRN 1/f are thermal and flicker input ise components of the preamplifier's core and s the input referred noise generated by the , R 1 .…”
Section: Recording Channelmentioning
confidence: 99%
“…The to c = 1 fF/µm 2 (it is a vailable technologies). ied by the recording ich may be assumed as 1 ). plifier, it was assumed ential pair work in the onductance is equal to old slope factor usually hermal voltage, I D is a that they are the major s the formulas for both…”
Section: Recording Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of object detection in biological systems is a non-trivial task and researchers are still in the process of decoding the neurological visual processes involved. Nevertheless, in [6,7,23], Baccus, Eizaburo, and Gollisch et al respectively argue that computations necessary for detecting object motion, distance, texture, and light are carried out in higher vertebrates' retinas before being passed to the brain for further processing. They argued that these functions are achieved by the photo-receptors using a combination of temporal filtering, threshold values and summing.…”
Section: Bio-inspired Visual Processing and Object Detection (Figure mentioning
confidence: 99%
“…It is quite likely that, in order to meet this critical window, the computations to achieve flocking in natural systems happen in or close to the retina [7,8]. For example, it has been observed that direction, light, object, texture, distance and motion detection all take place in mammal's retinas and not the visual cortex [6,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%